RESEARCH OF THE PHENOMENON OF VIOLENCE AND BULLYING IN SCHOOL (PANGEEA, 2025)
Violence and school bullying are just some of the manifestations of daily violence. More and more attention is being paid to violence and school bullying, facilitating public interest in youth violence, including violence and school bullying. The whole of society has become sensitive to violence and bullying in the school environment, abandoning the idea that school unity is an isolated space, unaffected by the difficulties faced by today's society.
Keywords: violence; bullying; pupils; school